The mechanism of chronic nicotine exposure and nicotine withdrawal on pain perception in an animal model. (10th January 2020) - Zhang, Yanping; Yang, Jinfeng; Sevilla, Alec; Weller, Robert; Wu, Jiao; Su, Chen; Zheng, Chumei; Rodriguez-Blanco, Yiliam F.; Gitlin, Melvin; Candiotti, Keith A
Graphical abstract: Highlights: Short-term exposure of nicotine induces mechanical hyposensitivity. Long-term exposure of nicotine results in hypersensitivity. Nicotine withdrawal induces hyperalgesia. Pain perception related molecules are affected by nicotine exposure. Abstract: It has been demonstrated that smoking is associated with an increase in postoperative and chronic pain. The changes in the pain-related neural pathways responsible for these effects are unknown. Additionally, the effects of nicotine withdrawal, resulting from smoking abstinence preoperatively, has not been evaluated in terms of its impact on pain sensation. In this study, an animal model has been used to assess these effects. A rat model of long-term nicotine exposure was used. Von Frey mechanical sensory tests were performed. Western Blot and immunohistological analysis were conducted on spinal cord samples. Mechanical sensory thresholds increased in the initial period (1–3 weeks), indicating hyposensitivity. Long-term (410 weeks) and under nicotine withdrawal, the mechanical sensory thresholds decreased, indicating hyperalgesia. During short-term nicotine exposure, glutamate decarboxylase 67 (GAD67), GAD65, and μ-opioid receptors (MOR) up-regulated. Beta-endorphins down-regulated. Increased γ -aminobutyric acid (GABA) and MOR appear responsible for the hyposensitivity since the GABA receptor antagonist, bicuculline and opioid receptor antagonist, naloxone decreased the mechanical thresholds of nicotine-induced hyposensitivity. In long-term nicotine exposure, the expression of GAD67, MOR, and GABA decreased. Baclofen, a derivative of GABA, reversed the hyperalgesia seen with nicotine withdrawal. Therefore, nicotine acts as an analgesic when used acutely or short-term. Long-term exposure or nicotine withdrawal (similar to smoking cessation) results in hyperalgesia. Nicotine appears to alter pain sensitivity by affecting the expression of GAD65, GAD67, MOR, endorphins, and GABA. This may partially explain the increased pain and opioid use seen in chronic smokers in the postoperative period.